The complete mitochondrial genome of Aglaia odorata, insights into its genomic structure and RNA editing sites - Hao, Zhigang; Zhang, Zhiping; Zhang, Jinan; Cui, Xiufen; Li, Jianqiang; Luo, Laixin; Li, Yingbin (Frontiers in Plant Science, 2024)
Aglaia odorata, native to Guangdong, Guangxi, and Hainan provinces in China, has long been utilized as an herbal remedy in ancient China. In this study, we assembled and annotated the complete mitochondrial genome (mitogenome) of A. odorata, which spans a total length of 537,321 bp. Conformation of the A. odorata recombination was verified through PCR experiments and Sanger sequencing. We identified and annotated 35 protein-coding genes (PCGs), 22 tRNA genes, and 3 rRNA genes within the mitogenome. Analysis of repeated elements revealed the presence of 192 SSRs, 29 pairs of tandem repeats, and 333 pairs of dispersed repeats in the A. odorata mitogenome. Additionally, we analyzed codon usage and mitochondrial plastid DNAs (MTPTs). Twelve MTPTs between the plastome and mitogenome of A. odorata were identified, with a combined length of 2,501 bp, accounting for 0.47% of the mitogenome. Furthermore, 359 high-confidence C to U RNA editing sites were predicted on PCGs, and four selected RNA editing sites were specially examined to verify the creation of start and/or stop codons. Extensive genomic rearrangement was observed between A. odorata and related mitogenomes. Phylogenetic analysis based on mitochondrial PCGs were conducted to elucidate the evolutionary relationships between A. odorata and other angiosperms.